Performance measurement of Islamic banking in Indonesia using the maqashid sharia index method - Adinda Lia Analia; Mohammad Bekti Hendrie Anto (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study aims to measure the performance of Islamic banking in Indonesia in 2014-2017 using MSI. This research is a quantitative descriptive study using the maqashid sharia index method, with 12 BUS as the object of research. The results of this research indicate that the highest MSI performance ratings were achieved by BPS (34.7%), BSB (32.6%) and BMI (31.6%), while the lowest rank was BTPNS. Islamic banking in Indonesia does not have consistency in applying maqashid sharia as a whole and has a fluctuating performance index. Another result is that the goal of achieving justice is Maqashid Sharia goal which is the main focus of Islamic banking in Indonesia in 2014 - 2017.